A Theoretical-Experimental Study of the Influence of FDM Parameters on PLA Spur Gear Stiffness - Zisopol, D. G.; Iacob, D. V.; Portoaca, A. I. (Engineering, Technology & Applied Science Research, 2022)
This paper studies the influence of FDM (Fused Depositing Modeling) parameters on gear stiffness made of Polylactic Acid (PLA). 3D printing parameters must be optimized because they influence the physical, mechanical, and quality characteristics of the additive manufactured part along with its functionality. The objective of this research is to optimize FDM parameters in order to obtain the highest stiffness. In this context, we used Finite Element Analysis (FEA) and we made experimental tests to validate its results. The experimental tests are divided into two categories, gears with the same parameters and gears with the same layer height and variable filling percentage. The average results of gear stiffness with the same parameters are 8.18% highest than the average results of gear stiffness with the same layer height and variable filling percentages.